Kryteria ekonomiczne, ekologiczne i etyczne zrównoważonego rozwoju - sprzeczność, komplementarność czy synergia? - Perepeczko, Barbara; Pieniążek, Witold (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
This paper tries to show that the sustainable development needs respecting close ecological, ethical and economic interactions constituting prerequisites for this phenomenon. It seems important to decide, if the sustainable development concepts are in essence closer to comprehensive, philosophical social systems or to the Smith's idea of desirable intervention of government rather, or maybe to the concept of man's well-being and the principle of assistance worked out on the ground of Personalism. There is no contradiction between economic, ethical and ecological aspects of sustainable development if it is based on the concept of meeting real needs of the population. One can consider the problem from the point of view of human activities in macro and micro scale, centrally governed or based on self-government. In practice, supplementation of those criteria is real only on the single firm level because of the better possibility to identify factual internalisation of ethical principles. It could be reached due to the concept of clienting, i.e. real but not only instrumental realisation of marketing rules.